Just another island dwarf? Phenotypic distinctiveness in the poorly known Soemmerring's Gazelle, Nanger soemmerringii (Cetartiodactyla: Bovidae), of Dahlak Kebir Island. (22nd February 2014) - Chiozzi, Giorgio; Bardelli, Giorgio; Ricci, Marcella; De Marchi, Giuseppe; Cardini, Andrea
<x xml:space="preserve">Abstract</x> The gazelles of Dahlak Kebir are the only population of Nanger soemmerringii Cretzschmar, 1828 living on an island. Little is known on the biology of these animals, except that they are evidently smaller than their conspecifics living on the continent. We took advantage of a recently acquired collection of crania, probably the largest available study sample of the Dahlak Kebir population worldwide, to explore the phenotypic variation of this island endemism. To this aim, we employed state of the art geometric morphometrics techniques and multivariate statistics to compare the insular population with samples of two out of three subspecies of N. soemmerringii from continental Africa. We found that not only is the size of the animal remarkably smaller in Dahlak Kebir gazelles, but their cranial shape is also highly distinctive, and this might be only partly explained by allometry. We also showed that phenotypic variance might have been reduced in the island population, likely as a consequence of genetic bottlenecks. This unique population is part of a species vulnerable to extinction. Our results suggest that the Dahlak Kebir Island gazelles might represent a significant component of its variation and potential for adaptive change and evolution. More information, including molecular data, and an accurate assessment of its taxonomic relevance and conservation status, is urgently needed. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 111, 603–620.